Tantangan Guru di Sekolah Islam dalam Penerapan Kurikulum Merdeka: Studi di MANU Putra Buntet Pesantren - Nasehudin, Nasehudin; Salsa Nabila; Fadel Ibnu Firmansyah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The implementation of the Merdeka Curriculum is a national education policy aimed at enhancing the quality of learning through a more flexible, student-centered approach that emphasizes character strengthening. However, the implementation of this curriculum in Islamic schools based on pesantren (Islamic boarding schools) presents unique challenges that require in-depth study. This research aims to describe the challenges faced by teachers in implementing the Merdeka Curriculum at MANU Putra Buntet Pesantren and to examine the school's readiness in supporting its execution. This study uses a descriptive qualitative approach with data collection techniques including observation, semi-structured interviews with the Vice Principal for Curriculum Affairs, and documentation. The results indicate that the Merdeka Curriculum has been implemented in grades X and XI, but its execution is not yet fully optimal. The main challenges faced by teachers include low student engagement in learning, demands for adapting to rapid policy changes from the government and the Ministry of Religious Affairs, as well as limitations in supporting learning facilities and infrastructure. Nevertheless, the character of MANU Putra Buntet Pesantren as an Islamic school based on pesantren serves as a strength in integrating Islamic values into learning. The implications of this research highlight the need for mentoring, more intensive socialization, and improved facilities to ensure the implementation of the Merdeka Curriculum in Islamic schools can be more effective and aligned with the objectives of Islamic education.